Effect of Brushing Time with a Whitening Dentifrice on Surface Roughness of Anterior Composite Resins - Hazar, Ahmet; Akgül, Sinem; Koçak, Sibel; Koçak, Mustafa Murat (UI Scholars Hub, 2022)
Objectives: This study aimed to compare the surface roughness of three anterior composite resins with different filler size, rate, and shape after brushing for 5000, 10000, and 20000 cycles with a whitening dentifrice. Methods: 44 disk-shaped specimens of each material (5mm diameter, 2mm depth) G-aenial Anterior, Harmonize, Asteria were prepared and divided into four groups according to the brushing cycles (Initial, 5000, 10000, and 20000 cycles). Initial surface roughness values (Ra-values) were assessed using a profilometer and measurements were repeated after each brushing cycle. 4 specimens from each composite resin were observed by scanning electron microscopy before and after brushing. The data were analyzed by Shapiro Wilk., ANOVA, Tukey, Friedman, and Wilcoxon tests (p<0.05). Results: The Ra-values of all groups increased in proportion to the number of brushing cycles (p<.05). The Ra-values of both Asteria and Harmonize were significantly lower than the G-aenial after all brushing cycles (p<0.05). Conclusion: All of the materials demonstrated surface irregularities after 20.000 brushing cycles corresponding to 24 months. The degree of surface alteration increased with brushing time and depends on the composite’s filler rate, size, and shape.